Re‐evaluation of pectin (E 440i) and amidated pectin (E 440ii) as food additives. (6th July 2017) - ,; Mortensen, Alicja; Aguilar, Fernando; Crebelli, Riccardo; Di Domenico, Alessandro; Dusemund, Birgit; Frutos, Maria Jose; Galtier, Pierre; Gott, David; Gundert‐Remy, Ursula; Lambré , Claude; Leblanc, Jean‐Charles; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Food Additives and Nutrient sources added to Food (ANS) was asked to deliver a scientific opinion on the re‐evaluation of pectin (E 440i) and amidated pectin (E 440ii) as food additives. An acceptable daily intake (ADI) 'not specified' was allocated by the Scientific Committee for Food (SCF) for E 440i and E 440ii. Pectin and amidated pectin would not be absorbed intact, but extensively fermented by intestinal microbiota in animals and humans; products formed from pectins in the gastrointestinal tract are similar to manufactured pectin‐derived acidic oligosaccharides (pAOS). There is no indication of genotoxicity for pectin and amidated pectin, although the available data were limited. No adverse effects were reported in a chronic toxicity study in rats at levels up to 5, 000 mg pectin/kg bw per day, the highest dose tested. No treatment‐related effects were observed in a dietary one‐generation reproductive toxicity study with pAOS in rats at up to 6, 200 mg/kg body weight (bw) per day, the highest dose tested. The Panel did not consider E 440i and E 440ii as having allergenic potential. A dose of 36 g/day (equivalent to 515 mg/kg bw per day) for 6 weeks in humans was without adverse effects. Exposure to pectins from their use as food additives ranged up to 442 mg/kg bw per day for toddlers at the 95th percentile (brand‐loyal scenario). The Panel concluded that there is no safety concern for the use of pectin (E 440i) and amidated pectin (E 440ii) as food additives for the general population and that there is no need for a numerical ADI.